2020
DOI: 10.1016/b978-0-444-64123-6.00007-2
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in language are small but matter for disorders

Abstract: Language is omnipresent in human life and therefore also in the brain. Gender differences in language can be signs of cognitive differences, but can also by themselves be the cause for such differences. Females have a slight linguistic advantage to males, but effect sizes are small and gender explains very little of the variance seen in the normal population (1-2%). However, males outnumber females in the lowest 10 th percentile in language tests (2:1), causing males to more often be diagnosed with development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 251 publications
1
23
0
Order By: Relevance
“…The sex differences in the efficacy of singing intervention reported by Kostilainen et al (2021) are not easy to interpret. Although gender differences are a highly debated topic, some results suggest that there is a small but noticeable difference in language development that females develop slightly faster than males ( Wallentin, 2020 ). However, it is unknown whether this is due to innate or genetic influences, or environment, since there is evidence that parents talk more to female than male children ( Leaper et al, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…The sex differences in the efficacy of singing intervention reported by Kostilainen et al (2021) are not easy to interpret. Although gender differences are a highly debated topic, some results suggest that there is a small but noticeable difference in language development that females develop slightly faster than males ( Wallentin, 2020 ). However, it is unknown whether this is due to innate or genetic influences, or environment, since there is evidence that parents talk more to female than male children ( Leaper et al, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…Findings have suggested that men are less lingually advanced than their female counterparts (Wallentin, 2020), which is said to be further exaggerated by offending status (Winstanley, Webb, & Conti-Ramsden, 2019). Apperly and Butterfill (2009), and more recently Meinhardt-Injac, Daum, Meinhardt and Persike (2018), noted that reflexive-cognitive processes (language) is required to understand the mental state of another person.…”
Section: Discussionmentioning
confidence: 99%
“…Language development may offer one explanation as to why an interaction between gender and offending status, in relation to verbal ToM, was found only in the male groups. Findings have suggested that men are less lingually advanced than their female counterparts (Wallentin, 2020), which is said to be further exaggerated by offending status (Winstanley et al, 2019). Apperly and Butterfill (2009), and more recently Meinhardt-Injac et al (2018), noted that reflexive-cognitive processes (language) is required to understand the mental state of another person.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, male children demonstrated poorer performance on oral language tasks (including language production and receptive vocabulary) than female children. Previous research also found that male children are at higher risk of language disorders than their female peers (Bendel et al, 1989;Norbury et al, 2016;Tseng et al, 2015;Wallentin, 2020). Thus, two separate hierarchical regression analyses were conducted for male and female children.…”
Section: T a B L E 1 Descriptive Statistics For All Variablesmentioning
confidence: 99%
“…After grammatical categories are assigned to words, infants infer probable meanings of novel words, as proposed in the syntactic bootstrapping hypothesis (Gleitman, 1990). Together, prosody helps chunk spoken sentences into small units (e.g., phrases or words), which would in turn enhance sentence parsing (Massicotte-Laforge & Shi, 2015, 2020 and novel word learning (de Carvalho et al, 2019).…”
Section: Prosody and Language Learningmentioning
confidence: 99%